Microarray Analysis of Gene Expression Reveals that Cyclo-oxygenase-2 Gene Therapy Up-regulates Hematopoiesis and Down-regulates Inflammation During Endochondral Bone Fracture Healing - Lau, K.-H. William (The Korean Society for Bone and Mineral Research, 2014)
BACKGROUND: Cyclo-oxygenase-2 (Cox-2) is an inflammatory mediator that is necessary for the tissue repair, including bone fracture healing. Although the application of Cox-2 gene therapy to a murine closed femoral fracture has accelerated bony union, but the beneficial effect was not observed until the endochondral stage of bone repair that is well after the inflammatory stage normally subsides. METHODS: To identify the molecular pathways through which Cox-2 regulates fracture healing, we examined gene expression profile in fracture tissues in response to Cox-2 gene therapy during the endochondral bone repair phase. Cox-2 gene therapy was applied to the closed murine femur fracture model. Microarray analysis was performed at 10 days post-fracture to examine global gene expression profile in the fracture tissues during the endochondral bone repair phase. The entire repertoire of significantly expressed genes was examined by gene set enrichment analysis, and the most up-regulated individual genes were evaluated further. RESULTS: The genes that normally promote inflammation were under-represented in the microarray analysis, and the expression of several inflammatory chemokines was significantly down-regulated. There was an up-regulation of two key transcription factor genes that regulate hematopoiesis and erythropoiesis. More surprisingly, there was no significant up-regulation in the genes that are normally involved in angiogenesis or bone formation. However, the expression of two tissue remodeling genes was up-regulated. CONCLUSIONS: The down-regulation of the inflammatory genes in response to Cox-2 gene therapy was unexpected, given the pro-inflammatory role of prostaglandins. Cox-2 gene therapy could promote bony union through hematopoietic precursor proliferation during endochondral bone repair and thereby enhances subsequently fracture callus remodeling that leads to bony union of the fracture gap.